Descartes intuitionniste ? - Frédéric de Buzon (Philosophia Scientiæ)
Descartes’ mathematical philosophy is sometimes identified with intuitionism. To appreciate this assertion, it is firstly necessary to understand the precise concept of intuition that Descartes elaborates in his great treatise on method, the Rules for the Direction of the Mind. Secondly it is then necessary to examine the interplay of intellectual operations capable of producing truth, namely intuition, deduction, and an operation that extends deduction which Descartes calls enumeration. We aim to show that intuition is certainly the norm of knowledge, but that real science, i.e., the ability to invent and solve any question, relies much more on the variety of deduction called enumeration.